The obligatory will between Iraqi law and Islamic jurisprudence - Basem Abdul Hussein Weni; Haider Jawad Kadim AlBaroud; Dr. Mahbouba Mina (Genius Journals, 2022)
We dealt with the subject of the obligatory will in this study based on Islamic jurisprudence and Iraqi law, as we initially explained the concept of the will in general, and we clarified the concept of the will and the extent of its legality in jurisprudence and law, as there was one approach that allowed it, which is the doctrine of zahirism, but from the majority of jurists, it became clear to us: The origin of the will is scarcity and desirability, and we discussed its legal and legal organization, as well as the conditions for its entitlement and the mechanism for its extraction and distribution to its beneficiaries, in two sections detailed with demands and branches, as it became clear to us after explaining the opinion of the zahirism (apparent) doctrine and the opinion of the majority of jurists about the legality of the obligatory will, the inadequacy of the zahirism (apparent) evidence about the necessity of this will in the right of those who inherit, as it became clear from the opinion of the majority of jurists, that any will on which the zahirism (apparent) basis was based on the legality of the obligatory will, has abrogated its obligation and remains desirable, and that the rule of the original will is scarcity and desirability and other mandated provisions have changed its secondary ruling
Keywords: Islamic; jurisprudence; zahirism; law